Spin-phonon coupling in multiferroic compounds obtained by high-pressure/high-temperature synthesis - Araújo, Bruno Sousa (2019)
The conventional solid-state reaction and under High-Pressure and High-Temperature methods were applied to synthesis of materials with interesting multiferroic properties. The melanothallite Cu2OCl2 was synthesized through conventional solid-state reaction in air atmosphere. We probed the spin-phonon coupling in Cu2OCl2 by Raman spectroscopy, showing that its incommensurate magnetic structure induces a spin-phonon coupling in accord with the mean field theory and it is similar to those observed in several stretching modes of perovskite compounds. In case of, the orthorhombic TmMnO3 perovskite, the samples were obtained through High-Pressure and High-Temperature treatment of the hexagonal phase of TmMnO3. The temperature-dependent Raman spectrum of orthorhombic TmMnO3 is reported showing the spin-phonon coupling at low temperatures. We also verified that the incommensurate antiferromagnetic ordering induces this spin-phonon coupling in according to the mean field theory and contrasting the assumptions in literature. In addition, we show that the coupling becomes null at the E-type antiferromagnetically ordered phase. The perovskite PbMn7O12 also was synthesized through high-pressure and high-temperatures technique presenting three magnetic transitions at 83, 72 and 38 K. Initial temperature dependent Raman spectrum analysis revealed renormalization effects on phonons frequency below 80 K, probably related to spin-phonon coupling. The pressure dependent behavior of PbMn7O12 perovskite also revealed possible phase transitions at 8.5 and 19.03 GPa. Finally, the High-Pressure and High-Temperature prepared monoclinic BiCrO3 perovskite present interesting properties with three anomalies of magnetic ordering founded around 40, 80 and 110 K. In this study, we report a strong spin-phonon coupling observed by Raman spectroscopy, showing that the G-type antiferromagnetic ordering induces the coupling in accord with the mean field theory similar to those observed in the several stretching modes of other perovskite compounds. In addition to the spin-phonon coupling, it was showed that all coupled phonons are also sensitive to the spin reorientation at 80 K and the magnetic anomaly around 40 K.